Depression and anxiety symptoms are associated with white blood cell count and red cell distribution width: A sex-stratified analysis in a population-based study. (October 2017) - Shafiee, Mojtaba; Tayefi, Maryam; Hassanian, Seyed Mahdi; Ghaneifar, Zahra; Parizadeh, Mohammad Reza; Avan, Amir; Rahmani, Farzad; Khorasanchi, Zahra; Azarpajouh, Mahmoud Reza; Safarian, Hamideh; Moohebati, Mohsen; Heidari-Bakavoli, Alireza; et al.
Highlights: Depression and anxiety disorders are associated with elevated levels of WBC; however, this association was only present in men. Depression and anxiety disorders also have a significant positive association with RDW which is much stronger among men. Depression also have a significant negative association with red blood cell (RBC) and mean corpuscular hemoglobin (MCH). Abstract: Background: Depression and anxiety are two common mood disorders that are both linked to systemic inflammation. Increased white blood cell (WBC) count and red cell distribution width (RDW) are associated with negative clinical outcomes in a wide variety of pathological conditions. WBC is a non-specific inflammatory marker and RDW is also strongly related to other inflammatory markers. Therefore, we proposed that there might be an association between these hematological inflammatory markers and depression/anxiety symptoms. Objective: The primary objective of this study was to examine the association between depression/anxiety symptoms and hematological inflammatory markers including WBC and RDW in a large population-based study. Methods: Symptoms of depression and anxiety and a complete blood count (CBC) were measured in 9274 participants (40% males and 60% females) aged 35–65 years, enrolled in a population-based cohort (MASHAD) study in north-eastern Iran. Symptoms of depression and anxiety were evaluated using the Beck Depression and Anxiety Inventories. Results: The mean WBC count increased with increasing severity of symptoms of depression and anxiety among men. Male participants with severe depression had significantly higher values of RDW (p < 0.001); however, this relationship was less marked among women (p = 0.004). In addition, men (but not women) with severe anxiety symptoms had significantly higher values of RDW (p < 0.001). Moreover, there was a negative association between red blood cell (RBC) and mean corpuscular hemoglobin (MCH) and symptoms of depression/anxiety. Conclusion: Our results suggest that higher depression and anxiety scores are associated with an enhanced inflammatory state, as assessed by higher hematological inflammatory markers including WBC and RDW, even after adjusting for potential confounders.